2019
DOI: 10.1002/jpln.201800465
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus deficiency promotes the lateral root growth of Fraxinus mandshurica seedlings

Abstract: This study aimed to evaluate the effects of phosphorus (P) deficiency on the lateral root growth of Fraxinus mandshurica seedlings and to reveal the potential molecular mechanisms involved. F. mandshurica seedlings were treated with various concentrations of P (0, 0.5, 1, and 2 mM KH2PO4) for 15 d. The growth of lateral roots was quantified by the number of lateral roots, total root length, total root surface area, and root : shoot ratio. Additionally, the levels of endogenous hormones and acid phosphatase wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…These results may be due to the impact of pruning on increasing the proliferation of roots that leads to an increase in the absorption of nutrients (Saifuddin et al, 2010). Regarding the enhancing effects of P-fertilizer on growth characteristics as reported by the present data, it may be due to the effects of P-fertilizer on improving the levels of plant hormones (IAA, GA 3 and cutokinins) which play pivotal roles in stimulating plant growth (Kahil et al, 2017;Huang et al, 2019). In contrast to the other nutrients necessary for plants, phosphorus is the least mobile and least available for plants under most soil conditions, whether acidic or alkaline because it is suitable for absorption in a certain range of soil pH (Ramaekers et al, 2010).…”
Section: Discussionsupporting
confidence: 58%
“…These results may be due to the impact of pruning on increasing the proliferation of roots that leads to an increase in the absorption of nutrients (Saifuddin et al, 2010). Regarding the enhancing effects of P-fertilizer on growth characteristics as reported by the present data, it may be due to the effects of P-fertilizer on improving the levels of plant hormones (IAA, GA 3 and cutokinins) which play pivotal roles in stimulating plant growth (Kahil et al, 2017;Huang et al, 2019). In contrast to the other nutrients necessary for plants, phosphorus is the least mobile and least available for plants under most soil conditions, whether acidic or alkaline because it is suitable for absorption in a certain range of soil pH (Ramaekers et al, 2010).…”
Section: Discussionsupporting
confidence: 58%
“…To improve plant adaptation to a range of stress, grafting scion varieties onto rootstocks is extensively employed for many woody economic species [35,36]. A great deal of research has been conducted on rootstock-induced changes in scion vigor [37][38][39], but there has been a lack of literature that has examined the influence of scion genotypes on biomass allocation and root development in grafted plants, especially under nutrient limitation. A previous study reported variety differences in spatial distribution and monthly dynamics of fine roots for five different cultivars of C. oleifera using the minirhizotron technique [29].…”
Section: Discussionmentioning
confidence: 99%
“…2e) and causing a decline in the solubility and the uptake of the macronutrients at par with micronutrients (Fig. 1 and 2), in particular, that P enhances root growth and architecture 34,35,36 , that consequently decrease the root e ciency and ultimately re ected in the reduction of peanuts agronomic traits (Fig. 3), and yield (Fig.…”
Section: Discussionmentioning
confidence: 99%